Lazarica in Sirinićka župa: Real and Action Component of the Ritual - Redžić, Emilija D. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
This paper is the result of the field research in the area of ​​Sirinićka župa, at the foot of Šara Mountain. The subject of the research is the description of the ritual called Lazarica, which is related to Lazarus Saturday. From the ethno-linguistic aspect, the real and action components of the ritual are analyzed, which provides insight into the ritual procedures and objects. Rituals are presented in the past and present, with all variants of the Lazarica ritual recorded in the field, in order to determine the differences caused by time, as well as folk beliefs and attitudes regarding different segments of the customary-ritual practice, in order to gain a more complete picture of cultural consciousness of the people in this area.
Keywords: ethno-linguistics; Sirinićka župa; Lazarus Saturday; Lazarica; custom; past; present